History textbooks as creators of national identity until the middle of the 20th century. The case of the first 'English invasions' - Fabian, Jorge Luis (Universidad Nacional del Litoral, 2022)
The investigations that use school textbooks as an object of study, obtained a greater relevance at the end of the 20th century, proposing a renewed look for the study of the History of education. In this same sense, the process of confirmation of citizenship from the construction of the idea of homeland has been raised in History school textbook mainly through the construction the ‘school anniversaries’. However, there are also other historical events that have been used for the same purpose, like the ‘english invasions’. For this reason, we believe it´s appropriate to review some history school textbooks published between 1896 and 1944 to observe how the first ‘english invasions’ was used to generate a sense of homeland in the criollos that led to the emergence of the first national government proclaimed on 25th may in 1810.